Dual fluorescent HPMA copolymers for passive tumor targeting with pH-sensitive drug release II: impact of release rate on biodistribution - Chytil, Petr; Hoffmann, Stefan; Schindler, Lucie; Kostka, Libor; Ulbrich, Karel; Caysa, Henrike; Mueller, Thomas; Mäder, Karsten; Etrych, Tomáš (Journal of controlled release, 2013)
In recent years, polymer drug carriers based on N-(2-hydroxypropyl)methacrylamide (HPMA) copolymers with pH-triggered drug release have shown enhanced uptake in solid tumors and excellent antitumor activity. Here, the impact of the structure of the acid-labile spacer between the drug and the polymer carrier on the biodistribution of both the drug and the carrier was studied using in vivo noninvasive multispectral optical imaging of dual fluorescently labeled HPMA copolymers. Five different spacers containing a pH-sensitive hydrazone bond were synthesized and used to combine a fluorescent model drug with a polymer backbone, conjugated with another non-releasable fluorescent dye. Two copolymers differing in polymer chain structure (linear and star-like) and molecular weight (30 and 200kDa) were used to distinguish between carriers with molecular weights above and below the limit for renal filtration. The rate of model drug release from the conjugates was determined in vitro. The biodistributions of the six most promising conjugates were investigated in vivo in athymic nude mice inoculated with human colon carcinoma xenograft. The structure of the spacer in the vicinity of the hydrazone bond significantly influenced the release rate of the model drug. The slow release rate of a pyridyl group bearing spacer resulted in a greater amount of the model drug being transported to the tumor, which was independent of the carrier structure. The results of this study emphasize the importance of careful selection of the structure and appropriate spacer when designing polymer conjugates intended for passive tumor targeting.
Keywords: Animals; Indoles; indoly; Fluorescent Dyes; Cell Line, Tumor; Hydrogen-Ion Concentration; akrylamidy; Tissue Distribution; Mice, Nude; nádory tračníku; lidé; pH-responsive drug release; Mice; Passive tumor targeting; fluorescenční barviva; myši; Tumor accumulation; Colonic Neoplasms; Models, Molecular; Multispectral optical imaging; léky s prodlouženým účinkem; Delayed-Action Preparations; molekulární modely; Male; Acrylamides; HPMA copolymers; Xenograft tumor model; myši nahé; tkáňová distribuce; karbocyaniny; zvířata; mužské pohlaví; koncentrace vodíkových iontů; Carbocyanines; nádorové buněčné linie; Humans